(3GdeLeY GdeDSS ddeYLe GdeagQSs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3ef Chd GdcJGH s
(3BNQgG (B:s
(3Edi Ydi Hf eMeO Hf eMeO s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B231 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCMeOjI HMdH (B(345) s
Keywords: (3GdJGQjNs